Effect of anticoagulants in pulmonary thromboembolism in post-covid-19 patients - BALABAN GENÇ, ZEYNEP CEREN (My University, 2023)
Background and objective COVID-19 may predispose to both venous and arterial thromboembolism (VTE and ATE) due to excessive inflammation, immobilization, and hypoxia. The purpose of this study is to evaluate clinical and laboratory risk factors, as well as related medications such as anticoagulants, to predict the risk of thromboembolic disease and/or death in COVID-19 patients. Methods Over a period of 14 months (from August 2020 to September 2021), a total of 145 consecutive patients with signs and symptoms suspicious of pulmonary embolism (PE) were referred for perfusion single-photon emission computed tomography/computed tomography (Q SPECT/CT). All patients had a history of SARS‑CoV‑2 infection, diagnosed with a positive real-time polymerase chain reaction (RT-PCR) test. Results Among the 145 patients included in the study, the risk of PE was found to be greater in elderly patients (odds ratio [OR] [95% CI]: 1.05 [1.02‑1.07]; p<0.001) and in patients with higher maximum d-dimer levels (OR [95% CI]: 1.14 [1.01‑1.3]; p=0.04). We also analyzed the utility of the maximum d-dimer level for predicting acute PE with receiver operating characteristic (ROC) curve analysis. For d‑dimer = 0.5 mg/dL, cut-off sensitivity is 91%, specificity is 23%, and for d-dimer = 1 mg/dL, cut-off sensitivity is 79%, specificity is 43% Conclusion D-dimer titers were higher in the PE group in our study. Another significant finding was that, possibly due to thromboinflammation, anticoagulants did not prevent the development of PE in COVID-19 patients.
Keywords: post-covid-19; d-dimer; anticoagulation; pulmonary thromboembolism; covid-19